2012
DOI: 10.1007/s00415-012-6618-z
|View full text |Cite
|
Sign up to set email alerts
|

Benign hereditary chorea: dopaminergic brain imaging in patients with a novel intronic NKX2.1 gene mutation

Abstract: Mutations in the NKX2.1 gene, which is essential for the development, differentiation and organization of the basal ganglia, cause benign hereditary chorea (BHC) characterized by childhood-onset non-progressive chorea. We herein report the clinical features of six patients from a single family with a novel intronic mutation and present the dopaminergic neuronal imaging by using positron emission tomography (PET) imaging to assess the integrity of the striatal dopaminergic system using [(11)C]-CFT for the presy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Previous reports showed the efficacy of levodopa for treating choreic movements in BHC, supporting the hypothesis that the dopaminergic neuronal system in the striatum is involved in its pathogenesis . We observed that levodopa/carbidopa also resulted in rapid improvement of both choreic movements and related drop attacks episodes in patient 1, while in patient 2 choreic movements and falls became less frequent over time without any treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Previous reports showed the efficacy of levodopa for treating choreic movements in BHC, supporting the hypothesis that the dopaminergic neuronal system in the striatum is involved in its pathogenesis . We observed that levodopa/carbidopa also resulted in rapid improvement of both choreic movements and related drop attacks episodes in patient 1, while in patient 2 choreic movements and falls became less frequent over time without any treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, the individuals in our series have been treated with a variety of oral therapies, none of which has provided significant improvement in their chorea. Previous studies have reported improvement with levodopa, ropinirole, and tetrabenazine, a partial response to propranolol, and worsening of symptoms with haloperidol . The lack of response in our cohort may be explained by the use of lower doses because of the development of intolerable side‐effects.…”
Section: Discussionmentioning
confidence: 57%
“…Additionally, a report of two related patients with BHC with an NKX2.1 mutation demonstrated reduced relative [ 11 C]-raclopride binding in the striatum with normal relative binding of 11-carbon-2 carbomethoxy-3-(4-[ 18 F]-fluorophenyl)tropane ([ 11 C]-CFT), a radioligand used to evaluate presynaptic dopamine transporter function [32]. This is rather surprising, as this disorder is not characterized by neurodegeneration affecting the neurons that bear dopaminergic receptors, but only of various interneurons [33].…”
Section: Reviewmentioning
confidence: 99%